2021
DOI: 10.1021/acs.chemrestox.1c00158
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study on Oxidative DNA Damage and Modifications by Haloquinoid Carcinogenic Intermediates and Disinfection Byproducts

Abstract: Haloquinones (XQs) are a group of carcinogenic intermediates of the haloaromatic environmental pollutants and newly identified chlorination disinfection byproducts (DBPs) in drinking water. The highly reactive hydroxyl radicals/alkoxyl radicals and quinone enoxy/ketoxy radicals were found to arise in XQs and H2O2 or organic hydroperoxides system, independent of transition-metal ions. However, it was not clear whether these haloquinoid carcinogens and hydroperoxides can cause oxidative DNA damage and modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 109 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…These radicals can cause breaks or mutations of DNA strands and result in cellular aging and cancer. 15,16 This type of radical In this study, our initial theoretical calculations suggested that the reaction of DCBQ and t-BuOOH encounters a high energy barrier and is energetically infeasible. An analogous high barrier has also been reported for the reaction between tetrachloro-1,4-benzoquinone (TCBQ) and neutral hydrogen peroxide (H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These radicals can cause breaks or mutations of DNA strands and result in cellular aging and cancer. 15,16 This type of radical In this study, our initial theoretical calculations suggested that the reaction of DCBQ and t-BuOOH encounters a high energy barrier and is energetically infeasible. An analogous high barrier has also been reported for the reaction between tetrachloro-1,4-benzoquinone (TCBQ) and neutral hydrogen peroxide (H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 95%
“…CBQ-O • then isomerizes to form quinone ketoxy radical • CBQO (see Scheme ). These radicals can cause breaks or mutations of DNA strands and result in cellular aging and cancer. , This type of radical generation mechanism may partly explain the carcinogenicity of halogenated aromatic compounds. Until now, the experimentally speculated reaction mechanism of DCBQ and t -BuOOH has not yet been confirmed by theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to disinfectants, the formed halogenated DBPs such as HAAs and haloacetonitriles could also select bacteria harboring iARGs. The ARGs encoding multidrug resistance in Pseudomonas aeruginosa increased by 1.49- to 2.92-fold after exposing to dibromoacetic acid . It was reported that the disinfectants and halogenated DBPs at both subminimum inhibitory concentrations (MICs) and above-MICs could select bacteria harboring iARGs with different mechanisms. , Sub-MIC levels of disinfectants or halogenated DBPs induce selection via enhanced horizontal gene transfer and cumulative mutations, which is associated with the generation of intracellular ROS. Above-MIC disinfectants or halogenated DBPs cause mutations and/or simultaneously enrich the pre-existing antibiotic resistance mutations with washing out of the susceptible species, which is ascribed to the similar resistance mechanisms (e.g., efflux pump) toward antibiotics and disinfectants or DBPs. …”
Section: Redistribution Of Iargs and Eargs In Disinfection Processesmentioning
confidence: 99%